Case reportPercutaneous balloon valvuloplasty because of bioprosthetic tricuspid valve stenosis - Kordybach, Maria; Kowalski, Mirosław; Demkow, Marcin; Hoffman, Piotr; Rużyłło, Witold (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
The durability of bioprosthetic valves is limited due to a process of mineralization and collagen degeneration over time. In a few years after surgery bioprosthesis dysfunction can occur and necessitate reimplantation. We would like to present a case of a patient with high risk of surgery, who underwent percutaneous balloon valvuloplasty of a stenotic tricuspid bioprosthesis.